Activities of Sordarins in Experimental Models of Candidiasis, Aspergillosis, and Pneumocystosis - Martinez, Antonio (American Society for Microbiology, 2000)
Sordarin derivatives represent a new class of antifungal agents that act as potent inhibitors of fungal protein synthesis and possess a broad spectrum of activity. The in vivo activity of GM193663 and GM237354 was studied in mouse models of disseminated candidiasis and aspergillosis and in a rat model of pneumocystosis. The pharmacokinetic behavior of both sordarin derivatives was studied in mice and rats. In all studies, compounds were administered by the subcutaneous route. After a subcutaneous dose of 50 mg/kg of body weight to mice, the maximum level in serum, area under the concentration-time curve, half-life, and clearance for GM193663 and GM237354 were 51.8 and 23 μg/ml, 79.5 and 46 μg · h/ml, 0.8 and 0.85 h, and 21 and 25 ml/h, respectively. Systemic candidiasis and aspergillosis were established in CD-1 male mice infected with Candida albicans or Aspergillus fumigatus. For systemic candidiasis, compounds were given three times per day for seven consecutive days at 15, 30, 60, or 120 mg/kg/day. GM193663 and GM237354 showed dose-related efficacy against C. albicans, with 50% effective doses, 1 month after infection, of 25.2 and 10.7 mg/kg/dose, respectively. In experimental infections with A. fumigatus, GM237354 was given three times per day at 30, 60, or 120 mg/kg/day for five consecutive days. Animals treated with GM237354 demonstrated irregular responses. The survival of animals treated with GM237354 was 0, 30, and 0% at 30, 60, and 120 mg/kg/day, respectively. The therapeutic efficacy of GM193663 and GM237354 against Pneumocystis carinii was studied in an experimental P. carinii pneumonia (PCP) rat model. After a subcutaneous dose of 10 mg/kg given to rats, the maximum level in serum, area under the concentration-time curve, half-life, and clearance for GM193663 and GM237354 were 6.6 and 7.2 μg/ml, 8.5 and 11.8 μg · h/ml, 0.7 and 0.8 h, and 230 and 133 ml/h, respectively. To induce spontaneous PCP, rats were chronically immunosuppressed with dexamethasone. Infected animals were treated twice daily for 10 days at 0.2, 2, or 10 mg/kg/day. The therapeutic effect was estimated by the reduction in the number of cysts in the lungs of treated versus untreated animals. GM193663 and GM237354 significantly reduced the mean (± standard deviation) log number of cysts from 7.6 ± 0.2 in the untreated group to 4.7 ± 0.2 and 4.6 ± 0.1, respectively, when the drugs were administered at a dose of 2 mg/kg/day. The log number of cysts was also reduced in infected animals given lower doses of the compounds (0.2 mg/kg/day). In summary, GM193663 and GM237354 are new sordarin derivatives that may potentially play a major role in the treatment of candidiasis and PCP. Further testing with Aspergillus in other animal models is warranted.